EDUKASI PENCEGAHAN STUNTING BAGI KELUARGA PENERIMA MANFAAT BANTUAN SOSIAL KAMPUNG POLAY KECAMATAN GAPURA - Enza Resdiana; Laylatul Hasanah (Dharma: Jurnal Pengabdian Masyarakat, 2021)
The success of the program to combat and reduce the number of stunting sufferers cannot be separated from the cooperation of all parties, as well as the support of all levels of society to promote stunting prevention. This reduction in the stunting rate also involves a conditional cash transfer program that provides a positive side in providing assistance and health services to Pregnant Women with Chronic Energy Deficiency (KEK), children under two years old and Toddlers. One of the government programs that is carried out continuously in reducing stunting rates in Indonesia is the conditional cash transfer program where the conditional cash transfer program is a social protection program that provides conditional cash assistance to beneficiary families who are required to carry out the terms and conditions that have been set. These requirements and conditions are contained in the Regulation of the Minister of Social Affairs which discusses the rights and obligations that must be carried out by the beneficiary. Health and nutrition campaigns and education for the community also need to be done, one of the things that can be done is to improve prevention and care services for children who have nutritional problems, special and sustainable handling needs to be done.